2004
DOI: 10.1161/01.cir.0000130844.01174.55
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous Coronary Intervention Results in Acute Increases in Oxidized Phospholipids and Lipoprotein(a)

Abstract: Background-This study was performed to assess whether oxidized low-density lipoprotein (OxLDL) levels are elevated after percutaneous coronary intervention (PCI). Methods and Results-Patients (nϭ141) with stable angina pectoris undergoing PCI had serial venous blood samples drawn before PCI, after PCI, and at 6 and 24 hours, 3 days, 1 week, and 1, 3, and 6 months. Plasma levels of OxLDL-E06, a measure of oxidized phospholipid (OxPL) content on apolipoprotein B-100 detected by antibody E06, lipoprotein(a) [Lp(a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

20
196
1
5

Year Published

2004
2004
2013
2013

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 233 publications
(222 citation statements)
references
References 41 publications
20
196
1
5
Order By: Relevance
“…The above results are also supported by the studies about ox-PL, which have demonstrated convincingly that a key ox-PL is preferentially associated with Lp(a) [52] and correlates with both the presence and extent of angiographically documented CAD [40,53], and their concentrations increase after ACS [51] and immediately after PCI [54].…”
Section: The Clinical Value Of Circulating Oxidized Lp(a)supporting
confidence: 63%
“…The above results are also supported by the studies about ox-PL, which have demonstrated convincingly that a key ox-PL is preferentially associated with Lp(a) [52] and correlates with both the presence and extent of angiographically documented CAD [40,53], and their concentrations increase after ACS [51] and immediately after PCI [54].…”
Section: The Clinical Value Of Circulating Oxidized Lp(a)supporting
confidence: 63%
“…15,16 Recognition of these oxidized phospholipids by a specific antibody, EO6 (an IgM autoantibody that recognizes the phosphatidylcholine head group in oxidized, but not in unoxidized, phospholipids containing arachidonic acid in the sn-2 position), has enabled them to be identified in atherosclerotic lesions in animals and humans. 28 The 12/15-lipoxygenase pathway, 15,16,29 -33 the 5-lipoxygenase pathway, 34 -36 the myeloperoxidase pathway, 37-43 the cycloxogenase pathways, 44 -46 and the NADPH oxidase pathways 47,48 have all been implicated in atherogenesis. The work of Blair et al 49,50 has shown that bifunctional electrophiles (␣, ␤-␤ unsaturated aldehyde genotoxins) such as 4-oxo-2-noneal can be formed from different lipid hydroperoxides by the action of trace metal ions or by vitamin C. The possibility that 4-oxo-2-noneal acts on LDL to produce biologically active oxidized phospholipids that are recognized by EO6 may explain how the genetic manipulation of multiple pathways producing different lipid hydroperoxides can influence atherogenesis.…”
Section: Role Of Oxidation In Atherogenesismentioning
confidence: 99%
“…OxPLs are highly prevalent in human vulnerable plaques ( 18 ) and in total chronic coronary occlusions ( 19 ). We have demonstrated that plasma OxPL/apoB levels identify angiographically-determined coronary artery disease (CAD) ( 14 ), predict the presence and progression of carotid and femoral atherosclerosis ( 20 ) and development of symptomatic peripheral arterial disease ( 21 ), and are elevated following acute coronary syndromes ( 12 ) and following percutaneous coronary intervention ( 22 ). Importantly, increased baseline levels of OxPL/apoB predict 15 year occurrence of new CVD events in previously healthy subjects independent of traditional risk factors and their Genetic architecture of PLG and apo(a).…”
mentioning
confidence: 99%